141 Coaching for Healthy AGEing trial – a cluster-randomised controlled trial. (20th November 2022) - Tiedemann, Anne; Oliveira, Juliana Souza; Allman-Farinelli, Margaret; Bauman, Adrian; Howard, Kirsten; Lindley, Richard; Lord, Stephen; Merom, Dafna; Rissel, Chris; Simpson, Judy; Tong, Allison; Wickham, James; et al.
Abstract : Background: Evidence shows that promoting physical activity among older people without providing fall prevention advice may increase fall rates. The Coaching for Healthy AGEing (CHAnGE) trial measured the effect of a physical activity and fall prevention program on physical activity and falls among community-dwelling people aged 60+. Design: Cluster-RCT involving 72 clusters (605 people). Methods: Participants were randomly assigned to control (35 groups; healthy eating intervention, involving education brochure and phone coaching) or intervention (37 groups; involving fall prevention/physical activity plan, one physiotherapist visit, phone coaching, pedometer, falls prevention advice, education brochure). Co-primary outcomes were: 1) Physical activity, objectively measured using ActiGraph GT3X, and 2) falls, recorded with monthly falls calendars over 12 months. Statistical analyses used linear regression (for physical activity) and negative binomial regression (for fall rates) to analyse between-group differences at 6 and 12 months. Results: Participants had a mean age of 74 years (SD 8.0). We found a significant between-group difference in physical activity at 6 months (mean difference=21.3 CPM/day, 95%CI 3.66 to 39.0) and a significant increase in steps/day in intervention versus control group at 6 months (649 steps/day, 95% CI 283 to 1015) and 12 months (460 steps/day, 95% CI 26 to 894). Intervention group reported a lower fall rate (193 falls, 0.71 falls/person/year, SD 1.09) than control group (229 falls, 0.87 falls/person/year, SD 1.80); difference was not statistically significant (IRR 0.86, 95% CI 0.6 to 1.1). Conclusion: A combined physical activity and fall prevention intervention significantly improved physical activity without increasing falls.